Musk (Moschus moschiferus) Attenuates Changes in Main Olfactory Bulb of Depressed Mice: Behavioral, Biochemical, and Histopathological Evidence - Almohaimeed, Hailah M.; Batawi, Ashwaq H.; Mohammedsaleh, Zuhair M.; Al Jaouni, Soad; Mutlq Alsawat, Samiah A.; Abd El Wahab, Manal G.; AbdElfattah, Amany A.; Ayuob, Nasra N. (Frontiers in Behavioral Neuroscience, 2021)
Background: Musk (Moschus moschiferus) has been described to have significant impact on the central nervous system as well as anti-convulsion and antidepressant effects. This study was designed to evaluate the efficacy of Musk in alleviating alterations induced in olfactory bulb of depressed mice exposed to chronic stress and identify the mechanism behind it. Methods: Fifty male albino mice divided in 5 groups (n=10 each); control, Musk, chronic unpredictable mild stress (CUMS), fluoxetine-treated and Musk-treated groups were included in this study. Behavioral changes and serum levels of corticosterone, pro-inflammatory cytokines included TNF-α, IL-6 and oxidant/antioxidant profile were assessed at the end of the experiment. Main olfactory bulb (MOB) has been processed for histopathological examination. Gene expression of caspase-3, glial fibrillary acidic protein (GFAP) and Ki67 were assessed in the MOB using qRT-PCR. Results: The study showed that Musk inhalation significantly reduced (p<0.001) corticosterone level, immobility time, inflammatory cytokines and oxidative stress markers in CUMS-exposed mice compared to the untreated CUMS group. Musk lessened CUMS-associated neuronal alterations in the MOB and significantly reduced apoptosis and enhanced neural cell proliferation (p<0.001) comparable to fluoxetine. Musk significantly enhanced the level of antioxidants in the serum and significantly reduced inflammatory cytokines. The anti-inflammatory and antioxidant activity of Musk and its constituents seemed to be behind its neuroprotective effect observed in this study. Conclusions: Musk effectively ameliorated the chronic stress-induced behavioral, biochemical as well as neuronal structural changes in MOB mostly through its antioxidant and anti-inflammatory effect.